Epigenetic tuning of PD-1 expression improves exhausted T cell function and viral control - Weiss, Sarah A.; Huang, Amy Y.; Fung, Megan E.; Martinez, Daniela; Chen, Alex C. Y.; LaSalle, Thomas J.; Miller, Brian C.; Scharer, Christopher D.; Hegde, Mudra; Nguyen, Thao H.; Rowe, Jared H.; Osborn, Jossef F.; et al. (Nature immunology, 2024)
PD-1 is a key negative regulator of CD8 + T cell activation and is highly expressed by exhausted T cells in cancer and chronic viral infection. Although PD-1 blockade can improve viral and tumor control, physiological PD-1 expression prevents immunopathology and improves memory formation. The mechanisms driving high PD-1 expression in exhaustion are not well understood and could be critical to disentangling its beneficial and detrimental effects. Here, we functionally interrogated the epigenetic regulation of PD-1 using a mouse model with deletion of an exhaustion-specific PD-1 enhancer. Enhancer deletion exclusively alters PD-1 expression in CD8 + T cells in chronic infection, creating a ‘sweet spot’ of intermediate expression where T cell function is optimized compared to wild-type and Pdcd1 -knockout cells. This permits improved control of chronic infection without additional immunopathology. Together, these results demonstrate that tuning PD-1 via epigenetic editing can reduce CD8 + T cell dysfunction while avoiding excess immunopathology. PD-1 is a critical modulator of CD8 + T cell activation and exhaustion. Sen and colleagues show that a cell-state-specific enhancer tunes PD-1 expression exclusively in exhaustion and that deletion of this enhancer improves CD8 + T cell function.